The role of institutional group in the empowerment of the family economy in the women farmers (KWT) in the District Of Central Lombok / Mukmin Suryatni ... [et al.] - Suryatni, Mukmin; Suparman, Lalu; Nasir, Mahyudin (2019)
Improve the well-being of the family is the main key to the people's welfare, there have been various efforts that have been undertaken by the Government, among other things, improve the role of women farmers group in the villages in order to improve the welfare of Members in particular and the community in general.